Globalisations in a nutshell: historical perspectives on the changing governance of the shea commodity chain in northern Ghana - Wardell, D.A.; Fold, N. (Ubiquity Press, Ltd., 2013)
Pre-colonial patterns of trade in West Africa included exchanges of shea in periodic local and regional markets. The collection, processing and marketing of shea products in such markets continues to be predominantly by women to both meet subsistence needs, and exchange of surpluses. In the early part of the 20th century, the British colonial administration considered the possibilities of starting large-scale exports of shea kernels to Europe. Multiple colonial initiatives to develop the global trade were not successful due to a composite of factors. Contemporary patterns of production, trade and regulation are contrasted in the context of globalisation in the post-independence era. The government of Ghana has progressively reinforced its ambitions to expand the shea nut trade as part of the state’s portfolio of major non-traditional agricultural export commodities. This policy is embedded within the (now) dominant orthodoxy of neo-liberalism, which privileges monetized production systems and private over public regulation. Historically and culturally-embedded patterns of shea production and trade by women in northern Ghana may now be challenged by the emergence of new processing technologies, the emergence of an oligopolistic global commodity chain and the anticipated continued growth in global demand for cocoa butter equivalents. Nevertheless, the cumulative impacts of increasing commercialisation and world market integration at the national and local level in Ghana, and other West African producer countries, are still unknown. There are risks, however, that this process may result in social differentiation, changes in household consumption patterns and loss of livelihoods, particularly for women.